Low Frequency Microstimulation Is Locally Excitatory in Patients With Epilepsy - Bartoli, Andrea; Tyrand, Rémi; Vargas, Maria I.; Momjian, Shahan; Boëx, Colette (Frontiers in Neural Circuits, 2018)
Deep brain stimulation (DBS) could become a palliative treatment for patients with drug-resistant epilepsy for whom surgery cannot be proposed. The objective of this study was to perform microstimulation to measure the effects of DBS in epilepsy locally at the level of a few neurons, with microelectrode recordings, for the first time in patients with epilepsy. Microelectrode recordings were performed before, during and after microstimulation in nineseven patients with refractory epilepsy. Neuronal spikes were successfully extracted from multi-unit recordings with clustering in 6 out of 7 patients during hippocampal and in 1 out of 2 patients during cortical dysplasia microstimulation (1 Hz, charge-balanced biphasic waveform, 60 micros/ph, 25 microA). The firing rates increased in 4 out of the 6 periods of microstimulation that could be analyzed. The firing rates and were found higher than before microstimulation in all 8 periods with increases reaching significance in 6 out of 8 periods. Low-frequency microstimulation was hence sufficient to induce neuronal excitation lasting beyond the stimulation period. No inhibition was observed. This report presents the first evidence that microstimulation performed in epileptic patients produced locally neuronal excitation. Hence neuronal excitation is shown here as the local mechanism of action of DBS. This local excitation is in agreement with epileptogenic effects of low-frequency hippocampal macrostimulation.